Friction welding of dissimilar plastic/polymer materials with metal powder reinforcement for engineering applications. (15th September 2016) - Singh, Rupinder; Kumar, Ranvijay; Feo, Luciano; Fraternali, Fernando
Abstract: Friction welding is one of the established processes for joining of similar as well as dissimilar polymer/plastics and metals. In past 20 years numbers of application in different areas using this process have been highlighted, but very limited contributions have been reported on properties of friction welded joints of dissimilar polymer/plastic materials after reinforcement with metal powder. In the present work an attempt has been made to perform friction welding of dissimilar plastic based materials by controlling the melt flow index (MFI) after reinforcement with metal powders. The present studies of friction welding for dissimilar plastic were performed on Lathe by considering three input parameters (namely: rotational speed, feed rate, and time taken to perform welding). Investigations were made to check the influence of process parameters on mechanical and metallurgical properties (like: tensile strength, Shore D hardness and porosity at joint). The process parameters were optimized using Minitab software based on Taguchi L9 orthogonal array and results are supported by photomicrographs.